Cosméticos: uma proposta de experimentação contextualizada por meio do enfoque CTS para alunos com deficiência visual no ensino de funções orgânicas - Oliveira, Mislene da Silva Gomes (2020)
Chemistry is a theoretical-practical science and vision is used as the majority sense. However, it must be considered that we all have differences, and the student with reduced or loss of ability to see may find limitations to participate actively and, consequently, to have effective learning. Therefore, claiming the democratic character in teaching chemistry, through pedagogical interventions using contextualization for study of organic functions, using contextualization under the STS (Science, Technology and Society) approach with the theme of cosmetics, with an emphasis on the social inclusion of these subjects. We have as theoretical basis the contributions of Historical-Cultural Psychology to education, focusing on students' autonomy, teacher mediation, the use of language and signs. As a methodological development we use action-research, seeking contributions with knowledge and experiences for the development of new strategies for teaching visually impaired students. Our results lead to a proposal for teaching chemistry that seeks new possibilities, using three principles of contextualization and five stages of the STS teaching approach, explaining a less visuocentric posture in experimentation and enabling the inclusion of these students in more autonomous participations for familiarize with tools and techniques specific to this culture, contributing to the teaching-learning process.